Financial disclosure and budgetary practices of religious organization: a study of qaryah mosques in Kuala Terengganu - Shaharuddin, Shahida; Sulaiman, Maliah (Universitas Gadjah Mada, 2015)
This paper aims to examine the financial reporting and budgeting practices of qaryah mosques in Kuala Terengganu, a state in the east of Peninsular Malaysia. Data was collected using a mixed method (quantitative and qualitative) approach. The questionnaire was disseminated to qaryah mosques in Kuala Terengganu and 39 responded. To address the limitations of a questionnaire survey, semi-structured interviews were then conducted with a few of the respondents. The results revealed that qaryah mosques in Kuala Terengganu do have a satisfactory system in place in terms of their financial reporting practices. However, budgetary control practices appear to be lacking. This indicates accounting, as is practiced by qaryah mosques in Kuala Terengganu appears to be limited to financial accounting. Hence, the financial management in qaryah mosques needs to be improved so that the risk of embezzlement can be reduced. Abstrak: Penelitian ini bertujuan untuk menguji pelaporan dan penganggaran praktek keuangan masjid-masjid qaryah di Kuala Terengganu, Negara bagian di timur Semenanjung Malaysia. Pengumpulan data dilakukan dengan menggunakan metode pendekatan campuran (kuantitatif dan kualitatif). Kuesioner disebarkan ke masjid-masjid qaryah di Kuala Terengganu dengan jawaban yang diterima sebanyak 39. Untuk mengatasi keterbatasan survei kuesioner, kemudian dilakukan wawancara semi-terstruktur dengan beberapa responden. Hasil penelitian menunjukkan bahwa masjid-masjid qaryah di Kuala Terengganu memiliki sistem yang memuaskan dalam hal praktek pelaporan keuangannya, namun, nampaknya kurang dalam praktik kontrol anggaran. Hal ini menunjukkan bahwa akuntansi, seperti yang dilakukan oleh masjid-masjid qaryah di Kuala Terengganu tampaknya hanya terbatas pada akuntansi keuangan. Oleh karena itu, manajemen keuangan di masjid-masjid qaryah perlu ditingkatkan sehingga risiko penggelapan dana dapat dikurangi. Keywords: accountability; budgets; financial reporting; qaryah mosques; religious organizations